Proceedings of the 41st Annual Hawaii International Conference on System Sciences (HICSS 2008) 2008
DOI: 10.1109/hicss.2008.13
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Comparison of Perceived Strategic Importance of RFID for CIOs in Germany and Italy

Abstract: Purpose: Drawing from literature on innovation, strategy and culture the objective of this study is to explore the role of perceived potentials and perceived strategic importance on CIOs' perspective on RFID technology in two different cultural settings. Methodology: Based on survey responses from 463 German and 157 Italian IT decision makers we analyzed the data with PLS structural equation modeling. Findings: We show that perceived potentials of RFID influence the perceived strategic importance which positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Our study used test of indicator validity criterion suggested by Straub et al (2004) to evaluate the reliability of our formative construct (Perceived trustworthiness of banks). Test of indicator validity refers to the importance of each individual indicator of the related formative construct (Jahner et al 2008;MacKenzie et al 2005), reflected by the significance of the path coefficient. Path coefficients from the indicators to the formative construct should be statistically significant under a t-test.…”
Section: Measurement Model Assessmentmentioning
confidence: 99%
“…Our study used test of indicator validity criterion suggested by Straub et al (2004) to evaluate the reliability of our formative construct (Perceived trustworthiness of banks). Test of indicator validity refers to the importance of each individual indicator of the related formative construct (Jahner et al 2008;MacKenzie et al 2005), reflected by the significance of the path coefficient. Path coefficients from the indicators to the formative construct should be statistically significant under a t-test.…”
Section: Measurement Model Assessmentmentioning
confidence: 99%
“…In this paper, we consider that RFID technology is an innovation and that it is innovative to integrate it with intra-and inter-organizational business processes and with intra-and internal information systems. As a reminder, RFID technology has the following characteristics: unique item/product level identification; no need of line of sight; multiple tags items reading; more data storage capability and data read/write capabilities (Asif and Mandviwalla, 2005;Jahner et al, 2008;Tajima, 2007), enabler of real-time data collection and sharing among supply chain stakeholders (Delen et al, 2007), enabler of business process innovation (Fosso Wamba et al, 2008;Lefebvre et al, 2006;Loebbecke, 2007). These characteristics may, therefore, be considered as influencing factors in the decision to adopt the technology.…”
Section: Literature Review 21 Innovation As Enabler Of Organization Transformationmentioning
confidence: 99%
“…As any emerging application, RFID at the item level is facing several obstacles towards massive consumer adoption. These obstacles include: high implementation costs, standards in early stages of adoption, privacy and security threats, low consumer acceptance levels, and reading reliability issues (Jahner et al (2008)). Dissemination activities have been organized worldwide with the aim of improving end-user knowledge of RFID technology and thus boost both acceptance levels and standard adoption.…”
Section: Introductionmentioning
confidence: 99%